To Explore the Risk and Return Performance for REITs Investment in Malaysia - Wee Win Yeoh (Westscience Press, 2023)
The rising popularity in investing in REITs investment had been increasing and capturing the preference among the Malaysian investors. This had addressed the problem statement for the study to further explore the study where the research is targeted to explore the risk and return performance for the REITs investment in Malaysia. With this, the quantitative study method had been suggested to explore the trend of the data input based on the timeline of 2013 to 2022 to explore the relevance performance of the REITs investment through eight different REITs collected for the sample study. In addition, the KLSE market index is included to explore the relationship against the REITs investment as well as providing comparative analysis to identify the discrepancies for the coefficient of variation performance with the REITs investment. The research findings had showed that the KLSE market index tends to provide significant positive impact towards the performance of the REITs investment return. Besides, the risk and return concept failed to showed the consistency to apply into the REITs investment and the comparative analysis unveiled the higher performance from REITs investment against the KLSE market index performance. The conclusion of the study had been drawn identifying the significant contribution towards the academic literature review as well as the future reference for investors when deciding to invest into REITs investment in Malaysia.